Actualized Utopias: The Here and Now of Transgender. Issue 2 (12th August 2016) - Nirta, Caterina
Abstract : "There's no need to fear or hope, but only to look for new weapons" (Deleuze 1992, 4) José Esteban Muñoz opens his book Cruising Utopia: The Then and There of Queer Futurity by stating that "queerness is not here yet. Queerness is an ideality … an ideality that can be distilled from the past and used to imagine a future." Queerness, continues Muñoz, "is a longing that propels us onward … Queerness is essentially about the rejection of the here and now" (2009, 1). He identifies queer utopias with an idea of futurity as an attempt to think of something else that goes beyond the "here and now, " an act of resistance: "the present is not enough. It is impoverished and toxic for queers and other people who do not feel the privilege of majoritarian belonging, normative tastes and 'rational' expectations … The present must be known in relation to the alternative temporal and spatial maps provided by a perception of past and future affective worlds" (27). In this article, I aim to show just the opposite. The argument I make here is that queer utopia—transgender—is a futurity of the here and of the now, a virtuality that does not belong to the past nor does it lend itself to projections of the future, but it is totally immersed in the very now of the present.